SINGLE CELL PROTEIN PRODUCTION BY ISOLATED AND IDENTIFIED BACTERIA USING CRUDE OIL AS A CARBON SOURCE - MOHAMMEDSALIH , KHOSHEE Q; HAIDER, MUSTAFA M (Journal of Duhok University, 2023)
In this study, we isolated and identified the bacteria from contaminated soil with crude oil, from different oil reservoirs of Duhok city, according to their morphological characterization and biochemical activity. The identification of bacterial isolates showed five different strains of bacteria, namely, Enterobacter cloacae, Serratia marcescens, Cronobacter sakazakii, Burkholderia cepacian, Raoultella ornithinolytica that are capable of degrading crude oil and have potential to grow on Bushnell-Haas Media (BHM). We also investigated the efficiency of the identified bacteria for consumption of crude oil as a single source of carbon and energy, and for production of single cell protein (SCP). The optimal conditions for bacterial growth, decomposition of crude oil and production of SCP were also determined. Our results showed that 48 hours of incubation and 0.75% concentration of crude oil were the most optimal for the biodegradation of crude oil, bacterial growth and for production of SCP. Additionally, it was noted the increase in the final pH of fermentation media of the five isolated bacteria owing to their metabolic activity leading to the producing substances which increase the final pH value more than the initial pH of the used media